VARIASI ECO-ANXIETY PADA MASYARAKAT PESISIR: BERDASARKAN USIA DAN GENDER - Kasim, Indah Luthfiyah; Kahar, Amalia S.J (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
This study aimed to examine the level of eco-anxiety among coastal communities based on gender and age. A quantitative survey was conducted with 117 respondents. Descriptive analysis showed that the majority of respondents were female (78.6%), with a higher average eco-anxiety score (Mean = 13.43, SD = 7.03) compared to males (Mean = 12.64, SD = 5.91). By age group, the highest score was observed in the 41–55 years category (Mean = 14.03, SD = 6.49), followed by the 21–30 years group (Mean = 13.52, SD = 7.03), while the 31–40 years group had the lowest score (Mean = 11.35, SD = 6.47). These findings indicate that females and older adults tend to exhibit higher levels of eco-anxiety. This may be explained by greater exposure to environmental information, higher awareness of climate change, and increased social responsibility among these groups. The results provide a basis for psychoeducational interventions aimed at promoting mental health in coastal communities.